Effectiveness of Early versus Standard Intrauterine Contraception following Medical 2 Management of First Trimester Incomplete Abortions: A Non-Inferiority Open-Label 3 Randomized Control Trial in central Uganda - Kayiga, Herbert; Looft-Trägårdh, Emelie; Kakaire, Othman; Cleeve, Amanda; Rujumba, Joseph; Sekikubo, Musa; Tumwesigye, Nazarius M.; Byamugisha, Josaphat; Gemzell-Danielsson, Kristina (My University, 2025)
Background: With paucity of information on ideal timing for intrauterine contraception placement, we set out to determine the effectiveness of early insertion (within one week) versus standard insertion (two-four weeks) of intrauterine contraception after medical management of first trimester incomplete abortions in central Uganda. Methods: In a multicenter non-inferiority trial at five public health facilities in central Uganda, 1,050 women with first trimester incomplete abortions managed by sublingual misoprostol, were recruited upon giving informed consent. After selecting either Copper or Levonorgestrel intrauterine devices (IUDs), participants were randomly assigned to early or standard insertion arms in a ratio of 1:1. The primary outcome was IUD expulsion rates at six-months. The non-inferiority margin was set at 5% for the upper limit of the confidence interval (CI) for the absolute risk difference. The trial was registered at ClinicalTrials.gov NCT05343546. Findings: Between 8th July 2023 to 31st May 2024, 528 (50·3%) participants were assigned to early and 522 (49·7%) participants to standard insertion arms. About 531 (50·6%) participants chose Levonorgestrel IUDs, 489 (46·6%) participants chose copper IUDs, while 30 (2·9%) participants opted against IUDs. In an intention-to-treat analysis, expulsion occurred in 23 (4·4%) of 528 participants in the early insertion arm and in 24 (4·6%) of 522 participants in the standard arm; Adjusted Risk Difference (standard-early) was -0·00006 (95% CI: -0·0008 to 0·00066, p = 0·93). No serious adverse events occurred in both arms. The IUD continuation rates at six-months were 91·1% in the early and 90·2% in the standard insertion arms. Interpretation: Early IUD insertion after medical treatment of first trimester incomplete abortions was non-inferior to standard IUD insertion with respect to expulsion. Early IUD insertion may help to prevent unintended pregnancies.